Determinan Perilaku Pacaran Sehat Pada Siswa di SMK Yarsi Medika Tigaraksa Kabupaten Tangerang Banten Tahun 2024 - Mozha Desri Puji Atuti; Febi Ratnasari; Siti Nurzzanah; Lita Anggraini (JURNAL BIDANG ILMU KESEHATAN, 2026)
The increase in sexual behavior among adolescents has become a significant issue in reproductive health in Indonesia. This condition is believed to be influenced by the ease of access to sexual content through digital media. Risky sexual behavior is now often perceived as normal by some adolescents who are in dating relationships. Data from the Indonesian Child Protection Commission indicate that 62.7% of adolescents in Indonesia have engaged in sexual intercourse, signaling a shift in norms within adolescent dating relationships. This study aimed to analyze the factors associated with dating behavior among students at an Islamic school in Banten Province. The study employed a quantitative approach with a cross-sectional design and was conducted from January to June 2024 at SMK Yarsi Medika. From a total population of 221 students, 145 respondents were selected using the Slovin formula, with data collected from both primary and secondary sources. The results showed that 24.8% of students exhibited unhealthy sexual behavior, while 75.2% were classified as having healthy sexual behavior. Bivariate analysis revealed associations between risky sexual behavior and knowledge, gender, place of residence, dating status, and peer influence. Further analysis indicated that peer influence was the most dominant factor, with an odds ratio (OR) of 2.6 after controlling for other variables.